Analisis kebutuhan pengembangan multimedia pembelajaran interaktif berbasis deep learning pada pembelajaran IPAS siswa SD - Tismiyati Tismiyati; Ifa Seftia Rakhma Widiyanti; Sita Isna Malyuna (Trihayu: Jurnal Pendidikan Ke-SD-an, 2026)
This study aimed to analyze the needs for developing deep learning-based interactive multimedia in Science and Social Studies (IPAS) learning for third-grade elementary school students. The study employed a descriptive quantitative approach involving 13 third-grade students at SD Negeri Terjan, Kragan District, Rembang Regency, selected using a saturated sampling technique. Data were collected through classroom observations and a pre-test. The data were analyzed using descriptive statistics and learning mastery percentage. The observation results indicated that the learning process still relied on the lecture method, learning media were limited to textbooks, students' active participation and learning motivation were low, and the available technological facilities had not been optimally utilized in the learning process. The pre-test results showed an average student score of 57.69. A total of five students (38.5%) met the Learning Objective Achievement Criteria (KKTP), while the remaining eight students (61.5%) had not yet achieved the criteria. The needs analysis indicated that Science and Social Studies (IPAS) learning requires deep learning-based interactive learning multimedia capable of presenting concepts concretely, enhancing students' active participation, and optimizing the utilization of available technological facilities in schools. This study provides a needs profile for the development of deep learning-based interactive learning multimedia, which can serve as an empirical basis for developing learning multimedia in future research.